Long-Term Effects of Kindergarten Vocabulary Instruction and Intervention on Target Vocabulary Knowledge Through Second Grade. Issue 4 (October 2022) - Coyne, Michael D.; McCoach, D. Betsy; Loftus-Rattan, Susan M.; Baker, Doris L.; Ware, Sharon M.
Abstract : We evaluated the long-term effects of a supplemental, small-group kindergarten vocabulary intervention in fall and spring of first grade and winter of second grade. Participants included students from two studies, an initial efficacy study and a subsequent replication study, identified as at risk for language and learning difficulties, who were randomly assigned in clusters to either a control group that received only classroom vocabulary instruction or a treatment group that received the classroom instruction plus small-group supplemental intervention. We also identified a group of not-at-risk students who received classroom vocabulary instruction as a reference group. Analyses using multilevel modeling indicated that students in the treatment group continued to outperform students in the control group on measures of expressive and receptive knowledge of words taught during the intervention through the winter of second grade, almost 2 years after the end of the intervention. Although long-term effects of the intervention on target word learning in second grade were substantial and meaningful, there was some deterioration of intervention effects across time. There were no effects of the kindergarten intervention on general vocabulary knowledge at posttest or any follow-up points. Findings suggest that the effects of direct and extended vocabulary instruction and intervention are generally durable and sustain over time for taught words.